The curated closet ebook A simple system for discovering your personal style and building your dream wardrobe. - Rees, Anuschka (2016)
Is your closet jam-packed and yet you have absolutely nothing to wear? Can you describe your personal style in one sentence? If someone grabbed a random piece from your closet right now, how likely is it that it would be something you love and wear regularly? With so many style and shopping options, it can be difficult to create a streamlined closet of pieces that can be worn easily and confidently. In The Curated Closet , style writer Anuschka Rees presents a fascinatingly strategic approach to identifying, refining, and expressing personal style and building the ideal wardrobe to match it, with style and shopping strategies that women can use every day. Using The Curated Closet method, you’ll learn to: • Shop smarter and more selectively • Make the most of your budget • Master outfit formulas and color palettes • Tweak your wardrobe for work • Assess garment fit and quality like a pro • Curate a closet of fewer, better pieces Including useful infographics, charts, and activities, as well as beautiful fashion photography,  The Curated Closet  is the ultimate practical guide to authentic and unique style.